ASSESSMENT OF PSYCHOLOGICAL PROBLEMS AND COPING STRATEGIES OF PERI-MENOPAUSAL WOMEN IN SELECTED DISTRICT OF WEST BENGAL - Hajra, Manisha; Choudhuri, Moitreyee; Maity, Chandrima (International Journal of Research -GRANTHAALAYAH, 2023)
Peri-menopause is natural event where ovarian follicular activity is reduced, for this reason women are prone to develop various physical and psychological symptoms. A descriptive study was conducted to detect psychological problems and coping strategies among peri- menopausal women in selected district of West Bengal. 200 participants were selected through non- probability purposive sampling technique to assess psychological problems and coping strategies among them and to find out the association between identified psychological problems and coping strategies with selected demographic variables. Conceptual framework of this study was based on Lazarus & Folkman’s Transactional Model of stress and coping. Semi-structured questionnaire, DASS 21 Questionnaire and Brief COPE Inventory were used to collect data. Result revealed that 63.5% peri- menopausal women had no depression, 2% had extremely severe depression. 71% had no anxiety; 55.5% had no stress and 10% had severe stress. Most of the peri- menopausal women (57.5 %) adopted moderate coping strategies. Chi-square test revealed that there was significant association between depression and educational status (p< 0.05). Coping strategies were also significantly associated with their monthly family income (p<0.05).